O poder de polícia no juízo eleitoral: a constitucionalidade na apuração administrativa de ilícitos pelo poder judiciário que possam ocasionar processos judiciais - Pereira, Kate Cibele Costa (2013)
This study aims to examine the constitutionality of the act of the electoral magistrates that judge cases which facts were narrated in the initial that was object of the restriction by police power used by them in their administrative function to preserve and oversee the smooth conduct of the electoral process. This power is assured to electoral judges in the current Electoral Code, Law nº 4.737/65, which has been received for the Federal Constitution of the 1988, which appointed a complementary law to define the electoral powers. Asked about this in 2006, the Superior Electoral Court decided that this not affront the impartiality, deciding for the constitutionality of the junction of powers, adopting as a premise the uniqueness of Electoral Justice. However, what is asked is precisely this assumption that has remained despite our Constitution point to another sense, of the guarantees of due process and observer of the principles listed in it. Therefore, brings an explanation of how the electoral powers are delimited currently, and the nuances of police power that is given to electoral judges, comparing them to constitutional procedural principles for the analysis of their constitutionality. At the end, concludes that the assumption of uniqueness of Electoral Justice should be revised, adjusting the distribution of powers to a model of jurisdiction to ensure the due process. Therefore, proposes the solution of the incompatibility of powers agglutinated by creating a specific institute to adoption the administrative measures and election monitoring, as other countries do, as a way to keep a jurisdictional provision impartiality, closest, consequently, for the justice.